Determinant Analysis Of Completeness Of Bpjs Patients' Does On Returning Bpjs Claim Status To The Royal Prima Medan General Hospital In 2022 - Muhammad Aditya Jamin; Sri Lestari Ramadhani; Putranto Manalu; Ermi Girsang (CV. Inara, 2022)
The history of insurance in Indonesia has a very long process until finally, we can feel its benefits easily this time. Getting to know the history of insurance is very necessary so that we know very well the ins and outs of insurance that many we meet now. The purpose of the study is to find out the relationship factors Completeness of patient Files BPJS Outpatient Against Returns the Status of the claim by the BPJS Health city of Medan To Hospital Royal Prima type B Field the year 2019. The research was conducted in January of 2019. As for the population in this research, the status of the patient in the November 2018 BPJS party discharged as many as 50 patients. No relationship SEP BPJS Outpatient Patients Against Returns the Status of a claim, there is a relationship of the medical record of patients Towards Outpatient BPJS returns, there is a connection INT CBG's BPJS Outpatient Patients Against Returns the Status of a claim, there is a relationship of KIS BPJS Patients Outpatient Against Returns The Status Of The Claim. It is hoped the hospital should still pay close attention to and improve it so that the creation of quality service and high-quality in the hospital Royal Prima Medan.